Evaluation of Multiplex/Nested Polymerase Chain Reaction and Loop-Mediated Isothermal Amplification for Malaria Diagnosis in Southeastern Iran - Mirahmadi, Hadi; Shahrakipou, Azam; Mehravaran, Ahmad; Rahmati-Balaghaleh, Mansour; Zarean, Mehdi; Etemadi, Soodabeh; Shahraki, Mehdi; Solgi, Rahmat (The American journal of tropical medicine and hygiene, 2022)
Malaria is one of the most serious health problems in many countries, including Iran. Accurate diagnosis is important regardless of the elimination status of a country. A cross-sectional study was performed on 105 people who were suspected to be positive for malaria infection in Sistan and Baluchistan, Iran. Blood smears (thin and thick films) were stained with 10% Giemsa. DNA was extracted from the prepared thin and thick films for molecular methods. Multiplex/nested polymerase chain reaction (mn-PCR), loop-mediated isothermal amplification (LAMP), and light microscopy (LM) were compared with nested PCR (nPCR) as a gold standard. Of 105 subjects, 52 (49.5%), 58 (55.2%), 58 (55.2%), and 63 (60%) were positive for malaria by LM, nPCR, mn-PCR, and LAMP, respectively. The sensitivity, specificity, and kappa were 92.1%, 100%, and 0.9 for LAMP and 100%, 100%, and 1 for mn-PCR, respectively. Eight cases of coinfection ( Plasmodium vivax and Plasmodium falciparum ) that were not detected by LM method were diagnosed by mn-PCR and LAMP. In the present study, the high sensitivity and specificity of LAMP and mn-PCR indicate that these two tests are good alternatives to nPCR for malaria diagnosis